Efficacy of tranexamic acid on blood loss during bimaxilary osteotomy: A randomized double blind clinical trial - Abbas Karimi; Sussan Soltani Mohammadi; Mahboobeh Hasheminasab (Saudi Journal of Anaesthesia, 2012)
Background: Tranexamic acid has been used to reduce bleeding and the subsequent need for blood transfusion in many surgeries. Because orthognathic surgery can be associated with significant bleeding, this study evaluated the efficacy of prophylactic intravenous (IV) tranexamic acid on blood loss during bimaxillary osteotomy. Methods: Thirty-two consecutive patients, scheduled for elective bimaxillary osteotomy, were included in the study and 16 were randomly assigned to each group. They received tranexamic acid (20 mg/kg) or equal volume of placebo (normal saline) intravenously just before induction of anesthesia. Intraoperative blood loss, pre and post operative hemoglobin (Hb) and hematocrit (Hct) concentration, duration of surgery, hospital stay time, and rate of blood transfusion were recorded for each patient. Results: Intraoperative blood loss in the tranexamic group and control group were 585.9 and 790 mL respectively (P=0.008). Postoperative Hb concentration at the 6 th hour was greater in the tranexamic group (P=0.008). There was no significant difference in the Hct concentration between the study groups. There was no significant difference in blood transfusion rate, hospital stay time and duration of surgery between the study groups. Conclusion: Preoperative IV administration of tranexamic acid reduces the amount of blood loss during bimaxillary osteotomy.